2010
DOI: 10.3109/17482961003605788
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral challenges in caring for patients with frontotemporal dementia and amyotrophic lateral sclerosis

Abstract: Frontotemporal dementia (FTD) is a progressive neurological condition caused by degeneration of the frontal and/or anterior temporal lobes resulting in personality, behavioral, and cognitive changes. Amyotrophic lateral sclerosis (ALS) is caused by degeneration of lower motor and pyramidal neurons, leading to loss of voluntary muscle movement. The common molecular pathological and anatomical overlap between FTD and ALS, suggest that the two disorders are strongly linked. In some patients FTD precedes ALS, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 26 publications
0
44
0
5
Order By: Relevance
“…Environmental modification refers to altering aspects of a person's environment for a range of reasons which may include safety (e.g., removing power tools from a shed), behavioural management (e.g., shutting the curtains during school hours to prevent inappropriate interactions with students), or assisting with engagement (e.g., removing any items not relevant to a task to prevent distraction) (Merrilees, Klapper, Murphy, Lomen-Hoerth, & Miller, 2010;Yokota et al, 2006). Communication strategies involve a range of techniques to assist the person with FTD to understand, and also to assist the person to be understood.…”
Section: Ppa Disability and Therapeutic Recommendationsmentioning
confidence: 99%
“…Environmental modification refers to altering aspects of a person's environment for a range of reasons which may include safety (e.g., removing power tools from a shed), behavioural management (e.g., shutting the curtains during school hours to prevent inappropriate interactions with students), or assisting with engagement (e.g., removing any items not relevant to a task to prevent distraction) (Merrilees, Klapper, Murphy, Lomen-Hoerth, & Miller, 2010;Yokota et al, 2006). Communication strategies involve a range of techniques to assist the person with FTD to understand, and also to assist the person to be understood.…”
Section: Ppa Disability and Therapeutic Recommendationsmentioning
confidence: 99%
“…Up to fifty percent of people with MND will develop neurobehavioral symptoms, from a subtle cognitive decline to serious impairment (30). Apathy, executive dysfunction and disinhibition are the most common neurobehavioral symptoms of patients reported by caregivers (30,31).…”
Section: Cognitive and Neurobehavioral Declinementioning
confidence: 99%
“…Apathy, executive dysfunction and disinhibition are the most common neurobehavioral symptoms of patients reported by caregivers (30,31). In about 15% of cases, people with MND will develop frontotemporal dementia which presents additional challenging neurobehavioral symptoms for family caregivers including irritability, impulsivity, loss of insight, self-centeredness and lack of empathy, aggression, food cravings, and obsessions and/or compulsive behaviors (30). A German study found burden is markedly higher in MND caregivers who report encountering "problem-behavior" (32).…”
Section: Cognitive and Neurobehavioral Declinementioning
confidence: 99%
“…At later stages, FTD patients develop deficits in executive function: they have problems planning, coordinating and executing simple tasks (Harciarek and Cosentino, 2013;Huey et al, 2009;Johns et al, 2009;Moy et al, 2004;Stopford et al, 2012). In addition to the characteristic behavioral changes, the clinical features of FTD can be complicated by neurological signs, such as motor neuron signs, parkinsonism, and gait disturbances, with some patients developing motor problems resulting from motor neuron pathology (Devenney et al, 2015;Merrilees et al, 2010).…”
Section: Introductionmentioning
confidence: 99%